Assessment of nutritional status of children (12-36 months of age) in urban area of district Rohtak, Haryana: a cross-sectional study - Kalhan, Meenakshi; Kaushal, Pankaj; Chayal, Vinod; Sachdeva, Aman; Yadav, Garima; Phogat, Vinay; Bansal, Kanika; Bansal, Kanika; Kaushik, Anil (International Journal Of Community Medicine And Public Health, 2021)
Background: Children 1-3 years of age are most vulnerable to the vicious cycles of malnutrition, disease/infection and resultant disability all of which influence the present condition of a child at the microlevel and the future human resource development of the nation at the macrolevel. Methods: Urban field practice area attached to the department of community medicine, Pt. B. D Sharma PGIMS, Rohtak being served by 14 anganwadi centres out of which 8 anganwadi centres were selected randomly. From each selected anganwadi centre, 22 children of 1-3 years of age group were selected by simple random sampling, thus, a sample of 176 children were included in the study. Results: Overall prevalence of undernutrition in our study was found as follows: wasted 14.1%; underweight 20.0%; stunted 24.1%. Inverse relation between prevalence of undernutrition and educational status of mother was observed. Children who were >3 in birth order had high prevalence of wasting, stunting and underweight. Children with low birth weight were having higher percentages of wasting, stunting, and underweight. Children who took supplementary nutrition regularly from AWC were less likely to be undernourished. Conclusions: Every endeavor should be made to combat the outcomes of undernutrition through multipronged approach such as growth monitoring, nutritional supplementation etc., Also, present study findings reinforce the importance of proper infant and child feeding practices and appropriate maternal care in prevention of childhood undernutrition.